Analysis of Nutritional Composition and Antioxidant Activity of Yogurt Enriched with Butterfly Pea (Clitoria ternatea L.) Extract - Yulia Windarsih; I Made Budiarsa; Manap Trianto; Akram Akram; Abdul Ashari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
The growing demand for functional foods has encouraged the development of dairy products enriched with natural bioactive ingredients to improve nutritional value and health benefits. This study aimed to analyze the nutritional composition and antioxidant activity of yogurt enriched with butterfly pea (Clitoria ternatea L.) extract. Yogurt was prepared from fresh goat milk with varying concentrations of butterfly pea extract and evaluated for protein, fat, carbohydrate, moisture, ash, vitamin C contents, antioxidant activity, and sensory acceptance. Proximate analysis, UV–Vis spectrophotometry, and the DPPH method were used for chemical determinations, while a hedonic test assessed color, taste, aroma, and texture. Results showed that increasing butterfly pea extract significantly decreased protein and fat contents but increased vitamin C and antioxidant activity, with the highest values observed in yogurt containing 60% extract and 4% formulation (N60K2). Moisture and ash contents were not significantly affected. Sensory evaluation indicated that yogurt with 60% extract and 2% formulation (N60K1) was preferred regarding color, taste, aroma, and texture. Considering compliance with the Indonesian National Standard (SNI) and consumer acceptance, N60K1 was the optimal formulation. The findings suggest that butterfly pea extract can enhance the functional properties of yogurt, particularly its antioxidant potential, while maintaining acceptable sensory quality. This provides insights for developing functional dairy products with natural plant-based bioactives.